Doing Feminist, Human Rights-Based, Socio-Legal Research on Prostitution: Challenges and Potential - Radacic, Ivana (feminists@law, 2016)
This article discusses the dilemmas faced in my research on prostitution. After describing the projects I have been undertaking in New Zealand and Croatia, it discusses the methodological and ethical issues I have been facing and the relevance of the legal and socio-cultural environments. In particular, it looks at the problems in securing access to the field and recruiting participants, the relationships with the participants, and the risks faced by the participants and the researcher. Following this, it summarises the lessons learnt and contributions that feminist socio-legal research centred on human rights can make for sex work scholarship.